Reconciling the short and the long run: governance reforms to solve the crisis and beyond - Karl Aiginger; Olaf Cramme; Stefan Ederer; Roger Liddle; Renaud Thillaye (WWWforEurope, 2012)
The policy brief is the first outcome of the four-year project 'Welfare, Wealth and Work for Europe' which started in April 2012 and aims at providing the analytical basis for a new European growth path towards a socio-ecological transition. It identifies the blind spots of the institutional changes embarked on by the EU in the aftermath of the sovereign debt crisis, and puts forward a combination of short-term and long-term measures in order to make an exit strategy compatible with the requirements of an economically dynamic, socially inclusive and ecologically sustainable Europe. The first section analyses the main features of the reformed governance framework and shows that the recent push towards integration does not fundamentally correct the flawed and self-contradictory features of Maastricht's institutions. A second section weighs different exit strategies and shows that the short-term logic of insurance and adjustment needs to be completed by the long-term vision of a sustainable economic union. The option of a smaller Eurozone is not considered as a viable road for all the economic and political costs it represents. The final section formulates recommandations to EU policy-makers with the view both to overcome the debt crisis and to lay the ground for a socio-ecological transition in Europe. In doing so, it pays particular attention to three kinds of trade-offs and tensions that have emerged throughout the crisis: the potential clash between adjustment and social cohesion ; the uncertainty on how to combine a more integrated Eurozone with a Community-based EU-27; the conflicting demands for more sovereignty and more democracy against a backgroung of deeper integration.
Keywords: E02; 330; good governance; competitiveness; ecological excellence; institutional reforms; economic strategy; EU integration; European economic policy; European governance; multi-level governance